Governance failure dalam kebijakan bantuan alsintan di indonesia: telaah kritis atas distribusi, akuntabilitas, dan risiko klientelisme - Tardi Setiabudi; Tino Supriantino; Agus Hiplunudin; Muharam Albana; Henry Dean Kresna (Jurnal Pengetahuan dan Pendidikan, 2026)
Agricultural machinery assistance is a strategic instrument in Indonesia’s agricultural modernization agenda. The program is intended to improve farming efficiency, reduce production costs, accelerate farm operations, and widen farmers’ access to agricultural technology. However, the effectiveness of such assistance depends not only on the number of machines distributed but also on the quality of governance shaping planning, beneficiary targeting, distribution, utilization, and oversight. This article examines governance failure in Indonesia’s agricultural machinery assistance policy through three dimensions: distribution, accountability, and the risk of clientelism. It applies a critical literature review approach to open-access publications from 2022–2026 on agricultural mechanization, local government capacity, performance accountability, transparency, and political clientelism. The review shows that the core problems of agricultural machinery assistance are not merely technical but also institutional and political. Distribution becomes vulnerable to mistargeting when beneficiary verification is weak and local implementation capacity is limited. Accountability often remains procedural rather than oriented toward actual utilization and outcomes. In addition, because agricultural machinery assistance is materially valuable and politically visible, it may be vulnerable to patronage and clientelist intervention at the local level. The article argues that reforming agricultural machinery assistance requires transparent, accountable, utilization-based governance and stronger safeguards against transactional political interference.